A nursing perspective on barriers to implementing harm reduction in acute care hospital settings: A scoping review / Un point de vue infirmier sur les obstacles à la mise en application de la réduction des méfaits dans les établissements hospitaliers de soins aigus : un examen exploratoire - Furlong, Kaitlyn; Li, Hua; Bigalky, Jodie (Canadian Journal of Emergency Nursing / Journal canadien des infirmières d’urgence, 2025)
While harm reduction has been implemented in some community health settings across Canada, they have been underutilized in managing in-patient environments. When patients with substance use disorder (SUD) are hospitalized, without harm reduction approaches, they may engage in risky behaviours, leading to unsafe substance use. Negative encounters with the healthcare system and nurses’ discriminatory attitudes toward patients with SUD also contribute to health issues and safety concerns. These include sharing syringes and using illicit drugs alone, which increase the risk of infectious disease transmission, overdoses, and death. This study reviewed existing literature on barriers to implementing harm reduction in acute care hospitals. Three databases were searched for peer-reviewed articles published from 2014 to 2024. After screening 987 articles, 10 met the inclusion criteria. The findings highlighted challenges nurses and patients encounter in implementing harm reduction in acute care hospitals, including stigma, safety concerns, knowledge gaps, and nurse burnout. Addressing these challenges entails nurse education and organizational changes. While the current research provides some insights, to enhanceharm reduction strategies in in-patient settings, further studies should examine standardizing care plans for individuals with SUD, healthcare agencies’ roles in promoting harm reduction education, and nurses’ perspectives.